Application of the finite element method for evaluating the stress due to operating load in high energy piping system - Mahardhika, Pekik; Husodo, Adi Wirawan; Budiyanto, Ekky Nur; Alfanda, Benedicta Dian; Sandora, Rina (Institut Teknologi Sepuluh Nopember, 2025)
The stress value of the piping system will change during operating conditions. The stress value affects the integrity of the piping system. Excessive stress will cause deformation and damage to the piping system. The operating condition parameters of the piping system are temperature and pressure. The High-Energy Piping (HEP) system is subjected to high pressures and temperatures, which can cause significant stresses on the piping components. So stress analysis needs to be carried out to ensure that the piping system has strength and flexibility. The Cold Reheat Pipe (CRP) steam line is one of the High-Energy Piping Systems in this steam power plant. CRP consists of CRP BS 130 and CRP BS 131. This paper is about evaluating the stress due to operating loads in 2024 (temperature, pressure, and remaining thickness) for steam lines on the high-energy piping system using the finite element method and refers to ASME B31.1. The output stress values in the piping system in this paper consist of stress due to sustained load, stress due to thermal load, and hoop stress. The CRP BS 130 modeling results show the maximum stress due to sustained load (166.6 kg/cm2), the maximum stress due to the thermal load (112.8 kg/cm2), and the maximum hoop stress (855.6 kg/cm2). The CRP BS 131 modeling results show the maximum stress due to sustained load (974.2 kg/cm2), the maximum stress due to the thermal load (123.5 kg/cm2), and the maximum hoop stress (938.9 kg/cm2). The results of the stress evaluation due to the operating load were still below the allowable stress and are still permitted by the ASME B31.1 Code.